Neural Tube Defects Role of Folate, Prevention Strategies and Genetics - Laksmi Narasimhan, Kannan (IntechOpen, 2012)
The book Neural Tube Defects - Role of Folate, Prevention Strategies and Genetics has several eminent international authors and the book is a resource for anybody who is interested in this very important subject. The authors are distinguished and the chapters are a product of their extensive research.